A household-scale life cycle assessment model for understanding the food-energy-water nexus - Daignault, Jessica; Wallace, Charles; Watkins, David; Handler, Robert; Yang, Yi; Heaney, Danielle; Ahamed, Sonya (Frontiers in Environmental Science, 2023)
The household is an important locus of decision-making regarding food, energy, and water (FEW) consumption. Changes in household FEW consumption behaviors can lead to significant reductions in environmental impacts, but it can be difficult for consumers to compare the relative impacts of their consumption quantitatively, or to recognize the indirect impacts of their household consumption patterns. We describe two novel tools designed to address this problem: a hybrida mixed-methods life cycle assessment (LCA) framework to translate household consumption of food, energy, and water into key environmental impacts including greenhouse gas emissions, energy use, and water use; and a novel software application called HomeTracker that implements the framework by collecting household FEW data and providing environmental impact feedback to households. We explore the question: How can a life cycle assessment-based software application facilitate collection and translation of household consumption data to meaningful environmental impact metrics? A case study in Lake County, Illinois is presented to illustrate use of the HomeTracker application. Output data describing environmental impacts attributable to household FEW consumption in the study area are shown in order to illustrate key features and trends observed in the case study population. The framework and its associated output data can be used to support experimental research at the household scale, allowing for examination of what users purchase and consume over an extended period of time as well as increased understanding of household behavior trends and environmental impacts, and as future work.